The Bibliometric Study of The Criptocurrency Literature in Scopus Database - Judijanto, Loso (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of cryptocurrency-related literature indexed in the Scopus database, aiming to map the intellectual landscape, identify key research trends, and highlight influential contributors in the field. Using VOSviewer as the primary analytical tool, the study examines keyword co-occurrence, temporal distribution, author collaboration networks, and international research partnerships. The findings indicate that the central focus of the literature remains on fundamental topics such as cryptocurrency, blockchain, and electronic money, while emerging trends show a growing integration of machine learning, forecasting, and sentiment analysis. Temporal mapping reveals a shift from infrastructure-oriented research to data-driven and interdisciplinary applications. Key authors and countries, including the United States, China, India, and the United Kingdom, play dominant roles in shaping the scholarly conversation. Despite the expanding scope of cryptocurrency research, gaps remain in areas such as sustainability, inclusivity, and ethical implications of AI applications. This study offers valuable insights for researchers, policymakers, and practitioners seeking to understand the evolution and future directions of cryptocurrency research.